Traditional medicines use among Indonesian young population: a Theory of Planned Behaviour study - Widayati, Aris; Rahajeng, Bangunawati; Wulandari, Erna Tri; Abadi, Barnabas Bagus Aditya (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Adolescents are a group that is very intensively exposed to changes from the Internet of Things, resulting in reduced exploration of nature, including medicinal plants. This study explores behavioral factors related to the use of herbals among Indonesian adolescents by applying the theory of planned behavior (TPB). The study was an analytic with a cross-sectional design. The independent variables were attitude, subjective norm, and perceived behavioral control. The dependent variable was behavioral intention. The samples were adolescents aged 10 to 19 years, determined from 200 samples in each of Indonesia's five major island groups, so 1,000 respondents were recruited. The instrument was a validated questionnaire that refers to the TPB constructs. Data were analyzed with a chi-square test and regression. 931 respondents participated in the research; the response rate was 93.1%. Approximately 85.1% of the participants expressed an intention to use traditional medicine. There is a statistically significant association between attitude, subjective norms, perceived behavioral control, and the purpose of using traditional medicine. The combined effect of the three constructs accounts for 25.9% of adolescents' propensity for using traditional medicines. All the factors contributed partially, with the subjective norm being the most significant contributor.